Evaluation via powder metallurgy of nano-reinforced iron powders developed for selective laser melting applications. (15th November 2019) - Mussatto, Andre; Groarke, Robert; A-Hameed, Ahmed; Ahad, Inam U.I.; Vijayaraghavan, Rajani K.; O'Neill, Aidan; McNally, Patrick; Delaure, Yan; Brabazon, Dermot
Abstract: In this work, a gas atomised stainless steel AISI 316L powder was used as metal matrix and SiC was employed as a nano reinforcement. The powders were experimentally characterised to determine the effect of the morphology, size, and levels of reinforcement on the powder flowability. The powder was developed via the powder metallurgy route and the effect of material, process conditions and various levels of reinforcement were investigated through the microhardness of the sintered samples. Sintered samples produced from the 316L + SiC + PVA powder mixes presented improved hardness. Analysis of the Energy Dispersive X-ray measurements detected high intensity levels of carbon and silicon on the surface of the reinforced 316L particles. In terms of measured powder rheology, the 6 wt% SiC coated 316L provided the highest flowability of the prepared SiC coated 316L powders and a much higher flowability than the as received 316L powder. All prepared SiC coated 316L powders showed good flowability and highly repeatable powder rheology. The high degree of flowability was attributed to the particle spherical morphology, the narrow range of particle size distribution and also the coating of nano SiC particles on the 316L particles which were found to act in this case as a solid lubricant. A successful homogeneous and uniform reinforcement of SiC onto the surface particles was resultant from the established mixing technique. While the nano-SiC improved the powder fluidity, the obtained improvement in hardness was also due to the nano-SiC dissolution and resultant precipitates formed during the thermal treatment. Graphical abstract: Unlabelled Image Highlights: Powders were successfully developed via an optimised ball milling mixing technique. A uniform and consistent layer of SiC particles with a strong adherence onto the surface of the 316L particles was obtained. The developed SiC coated 316L powder presented superior flowability characteristics in comparison to the sieved 316L powder. The addition of nano SiC to 316L has significantly improved the hardness of sintered samples. Iron silicide and complex carbides precipitates resulted from the dissolution of SiC into the 316L matrix.